Torrefaction of coconut shells using a batch reactor in an oxidative environment - Tanchuling, Jes Francis M.; De Leon, Rizalinda L. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Torrefaction is a thermo-chemical treatment to address problems in use of biomass as a fuel especially for combustion; it is usually done between 200-300ºC in an inert or low oxygen environment. This study investigated the properties of Coconut Shell chips that were torrefied using a batch reactor in an oxidative environment at torrefaction temperatures of 250ºC and 300ºC, and torrefaction time of 30 minutes and 60 minutes. Analysis of solid products included Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Scanning electron microscope (SEM) observations, Higher Heating Value determination, Proximate Analysis, equilibrium Moisture Content (EMC) and Grinding Energy. Liquid products were analyzed in FTIR. The gas product composition was analyzed through gas Chromatography- Thermal Conductivity Detector (GC-TCD). Overall, the results in the solid product showed changes in composition, thermal degradation curve, and surface morphology; also improvement of fuel properties in terms of HHV, Fixed Carbon Content, Moisture Content, Equilibrium Moisture Content, and Grinding Energy. Among the settings, the 300 ºC and 30 minutes setting is recommended with significant improvement of the solid fuel and lesser energy input.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Coconut; Biomass -- Combustion; Plant biomass